2014
DOI: 10.1016/j.tox.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of air-delivered particle-bound polybrominated diphenyl ethers

Abstract: Human exposure to polybrominated diphenyl ether (PBDE) can occur via ingestion of indoor dust, inhalation of PBDE-contaminated air and dust-bound PBDEs. However, few studies have examined the pulmonary toxicity of particle-bound PBDEs, mainly due to the lack of an appropriate particle-cell exposure system. In this study we developed an in vitro exposure system capable of generating particle-bound PBDEs mimicking dusts containing PBDE congeners (BDEs 35, 47, 99) and delivering them directly onto lung cells grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…2). These findings confirm observations reporting that PBDE-99 within the same concentration range used in the present study did not produce cell damage in A549 cells (Kim et al 2014). Another report assessed DOPO toxicity in PC12 and B35 neuroblastoma cell models and also observed no damage using a concentration range comparable to that applied in the present study, further confirming the low cytotoxic potential of DOPO (Hendriks et al 2014).…”
Section: Resultssupporting
confidence: 94%
“…2). These findings confirm observations reporting that PBDE-99 within the same concentration range used in the present study did not produce cell damage in A549 cells (Kim et al 2014). Another report assessed DOPO toxicity in PC12 and B35 neuroblastoma cell models and also observed no damage using a concentration range comparable to that applied in the present study, further confirming the low cytotoxic potential of DOPO (Hendriks et al 2014).…”
Section: Resultssupporting
confidence: 94%
“…MicroSprayer® IA-1C aerosolizer for liquid aerosols and DP-4 Dry Powder Insufflator™ for powder aerosols have been used for intratracheal delivery of nanoparticles and occupational and environmental toxicants to mice and rats [63][64][65][66]. Both devices have also been used in cellular studies [35,61,[67][68][69][70][71][72][73][74]. Particle sizes produced by DP-4 Dry Powder Insufflator™ were linked to the respective sizes of the formulated or of the not-formulated powders [75] and are roughly similar before and after aerosolization [76].…”
Section: Exposure With Particlesmentioning
confidence: 99%
“…Emerging contaminants such as the flame retardants (polybromo-diphenil, PBDEs ethers) PBDE-47, -99, and -209 are widespread in indoor and outdoor environmental contamination. These substances are present in fabrics, electrical materials, dust; e.g., they induce pulmonary toxicity by promoting an inflammatory response in lung epithelial cells [ 43 , 44 , 45 ]. The same PBDE profile has been described in southern Europe by Besis et al [ 46 ], while Pozo et al identified, of 26 PBDEs routinely analyzed, the presence of three (PBDE-47, -99 and -100) in the coastal areas of Sicily [ 47 ].…”
Section: Environmental Pollution and Health Of Respiratory Systemmentioning
confidence: 99%